Os sentidos do trabalho para enfermeiros de um hospital geral filantrópico - Tiana Rita dos Santos Rodrigues (2006)
This qualitative nature work aims to understand the meaning of work to a groupof nurses working in a general philanthropic hospital , through the knowledge of characteristics of the work performed by them , the feelings involved , and the meanings disposed towards its performance. A qualitative study case has been chosen, in which the subjects were nurses working in a general philanthropic hospital. The data were collected through a semi-structured interview, submitted to speech analysis and the results were organized into two categories: The Context of Hospital Work and the Meanings of the Work to the Nurses. The results show that the nurses perform highly administrative tasks, followed by assistencial and educational and also that the research activities are, yet, incipient. They claim to be getting autonomy in the daily work , but face difficulties regarding the multiplicity of tasks performed, the wok load , the administrative body of the organization , qualitative and quantitative need of nurse staff , besides an intense moviment of companions and trainees in the institution. They report identification with the institution and show interest in the introduction of changes that aim to improve the quality of assistance. They are committed to the organizational goals, feel themselves fulfilled as nurses, though they sometimes find themselves frustrated for not being able to carry on with certain projects. Among all the factors that bring meaning to the work of nurses emerged the identification with the purpose of the profession, the possibility of being helpful, the possibility of learning and keeping updated, the feeling of affiliation, the wage, having an occupation, the acknowledgement from superiors, peers and subordinates, and the autonomy in the work as a nurse.